Mechanical performance reduction of GFRP specimens with polyester matrix exposed to continuous condensation. (15th August 2016) - Stazi, F.; Giampaoli, M.; Nisi, L.; Rossi, M.; Munafò, P.
Abstract: In this experimental study, GFRP small specimens and full-scale profiles with polyester matrix were exposed for six months to a constant temperature of 40 °C and relative humidity of 98–100%. The trend of absorption during the ageing treatment was evaluated and, after the exposure period, the mass increment and mechanical properties of aged specimens were compared to un-aged ones. Tensile tests were conducted on dog-bone geometries with different fiber orientations (0°, 45° and 90°), while squared tubular profiles were employed in flexural and torsional tests. The trend of absorption was found to be pseudo-Fickian and the weight increment was very similar for all the tested samples. The artificial ageing reduced the mechanical properties in the matrix dominant direction of GFRP profiles. In tensile tests, the ageing treatment produced different effects depending on specimen fiber orientations: the lowest strength and elastic modulus reductions (respectively of about 4 and 5%) were registered by those specimens tested along the direction of fibers (0°), which are only moderately affected by moisture and heat. The same failure modes in tension, before and after ageing, were observed for all fiber directions. Both torsional and flexural properties resulted to be significantly decreased (8%). In these latter loading types, the aged matrix is more involved in the failure mechanisms and this was confirmed by the failure modes that after ageing showed more evident fractures.